Association between mental health and social media addiction: Systematic review - Bustamante-Aguilar, Diana; Lira-Mandujano, Jennifer; Núñez-Lauriano, Mariana; Cruz-Morales, Sara (Journal of Basic and Applied Psychology Research, 2026)
Excessive use of social media (SNS) is associated with negative mental health consequences in young adults and adolescents. Therefore, the objective of this review is to systematize information from articles published in the last 5 years on the mental health consequences of social media addiction in adolescents and young adults. Articles published from 2019 to 2025, in English/Spanish, with adolescent and young adult populations were analyzed. The results showed that for adolescents, the mental health consequences were anxiety, depression, nomophobia, behavioral problems mainly with parents and relatives, sleep problems, and difficulty interacting in person. For young adults, the results showed negative sleep quality, symptoms of depression, anxiety, low self-esteem, negative self-comparison, stress, feelings of loneliness, and low perception of subjective well-being. In conclusion, it is important to continue research in this area, focusing on the long-term consequences of social media addiction. It is also important to understand the specific characteristics of social media that lead to continued uncontrolled use and to propose interventions that help improve management of social media use to avoid negative consequences